Analisis Kepuasan Pengguna Sistem Keuangan Desa Menggunakan Metode EUCS di Kabupaten Purbalingga - Retno Waluyo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
In the current era of technology and information, the government is trying to improve accountability and transparency to the public by launching a Good Governance program to be implemented at both the central and regional levels. at the village level The management of village funds must be managed with good governance in accordance with the principles of Good Governance so that there is no misuse in the use of village funds. Purbalingga Regency is one of the areas that has implemented SISKEUDES with 224 villages in Purbalingga Regency. Village Financial System application (SISKEUDES) to facilitate the management of APBDes. In its implementation, when using SIKEUDES, there are problems, including when filling in the data to the system, there are parameters that are not available, so that the system operator has difficulty in the process of filling in parameters. The purpose of this study is to analyze the factors that play a role in affecting the satisfaction of SISKEUDES operators in Purbalingga Regency using the EUCS method. The results of this study that the content, accuracy and format factors have no effect on SISKEUDES operator satisfaction, while easy of use and timeliness have an effect on SISKEUDES operator satisfaction in Purbalingga district. The resulting regression equation Y = 5,505 - 0,061X1 - 0,048X2 + 0,068X3 - 0,230X4 - 0,206X5